Engineering Physics : Theory and Applications - Faulkner, Erin (New York : NY Research Press, 2019)
Engineering physics combines the disciplines of physics, mathematics and engineering for the design, development and application of new technological solutions to industry. All modern technologies and gadgets that are being used across the world are a result of tremendous research and engineering in this field. It integrates principles from the classical domains of optics, electronics, quantum physics, materials science, nanotechnology and solid state physics for applications in metallurgy, ballistics, cryogenics, polymers, advanced communication and instrumentation. This book discusses the fundamentals as well as modern approaches of engineering physics. It provides insightful ideas and new concepts and will be useful to students and experts associated with this domain.
Keywords: Applied physics